Chad : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
The note provides statistical data on gross domestic product, supply and use of resources, consumer price index, cotton production, cost structure of cotton processing and marketing, government revenue, economic classification of central government expenditure, public investment program, and monetary survey of Chad. The summary accounts of the central bank, balance sheet of commercial banks, balance of payments, foreign trade indices, exchange rates, and other related economic indices of Chad along with indicators of fiscal balance, external balance, and external public debt of CEMAC have been given.